New spatial strategy in China: major function zoning of Beijing-Tianjin metropolitan area with perspective from ecological economics - He, Jinliao; Zong, Yue-Guang; Gebhardt, Hans (Journal of urban planning and development, 2011)
Responding to contemporary environmental problems and to unbalanced regional development in China, major function zoning (MFZ) has been considered a new spatial strategy. This study attempts to explore the quantitative approach of MFZ on the basis of views from ecological economics, asserting that a comprehensive analysis of a regional integrated ecosystem can help identify MFZs. For this study, the development degree model was built, and the regional development factors were classified as potential-factors and constrain-factors. By applying this model, the comprehensive analysis of a regional integrated ecosystem was completed with the case study of the Beijing-Tianjin Metropolitan area. The analysis included factors of ecological sensitivity, environmental stress, socioeconomic development potential, and natural resource potential. Finally, the study area was divided into four MFZs. The results showed that the optimization zones, located primarily in the central areas of Beijing and Tianjin cities, occupied 4.2% of the total study area. The key development zones were distributed around the former optimization zones in a structure of rings and corridors, covering 23% of the total area. Restriction zones (51.4% of the total area) and prohibited zones (21.4% of the total area) were situated in the northern and southwestern parts of Beijing and the northeastern and southwestern parts of Tianjin. This quantitative study is expected to contribute to the development of theory and to the approach taken toward MFZ in China's metropolitan areas and elsewhere.
Gesehen am 18.12.2018